Buddy sebagai Digital Psychological Intervention berbasis token ekonomi bagi individu dengan ADHD - Azizah, Rosyta Nur; Anjarwati, Eli; Prabowo, Krisna Mukti; Hamidah, Hamidah (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
ADHD is a neurodevelopmental disorder defined by impairing levels of inattention, disorganization, and/or hyperactivity-impulsivity. The prevalence of ADHD is reported to continue increasing every year. In fact, the high need for ADHD children to get treatment is not matched by the availability of a number of psychologists. This makes hard for children with ADHD to access a psychologist due to limited reach and resources. Therefore, we need a tool that can help the therapy process. Buddy is a digital innovation that has a feature such as schedule lists, video role models, and a token shop that can make it easier for psychologists and parents to customize it. Psychologists can freely arrange intervention designs (schedule lists and rewards) according to criteria for ADHD children being handled. This study aims to find out how the prediction of the usefulness of the Buddy application prototype using the token economy approach through prototype visualization can solve the problem of ADHD child Intervention. The method used is research and development (R&D) which produces a UI design-based token economy procedure. This design generates 22 UI mock-up pages that represent the application model